Rethinking redistricting : how drawing uncompetitive districts eliminates gerrymanders, enhances representation, and improves attitudes toward congress - Brunell, Thomas L. (2006)
Contiene bibliografía
Keywords: Electorado; Candidato; Estados Unidos